1982
DOI: 10.1021/jm00352a015
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of the prosthetic heme in cytochrome P-450 during oxidative metabolism of the sedative-hypnotic ethchlorvynol

Abstract: The clinically used sedative-hypnotic ethchlorvynol destroys hepatic microsomal cytochrome P-450 enzymes in a process catalyzed by the same hemoproteins. Abnormal porphyrins accumulate in the livers of phenobarbital-pretreated rats after administration of ethchlorvynol. The abnormal porphyrin fraction has been isolated and shown to consist of the four possible regioisomers of N-(5-chloro-3-ethyl-3-hydroxy-2-oxo-4-pentenyl)protoporphyrin IX. Cytochrome P-450 inactivation thus appears to result from alkylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…However, whether the oxygen has been added to the internal or terminal carbon cannot be ascertained from the MS/MS spectrum. Ortiz de Montellano et al, (1982) have previously reported that if the oxygen atom is added to the internal carbon, the heme will be alkylated, and if the oxygen is added to the terminal carbon, the protein will be modified (Ortiz de Montellano and Komives, 1985;CaJacob et al, 1988;Chan et al, 1993). Because a protein adduct was identified in this case, the structure proposed for the GSH conjugate has the oxygen inserted into the terminal carbon as shown in Fig.…”
Section: Lc/ms/ms Analysis Of Gsh Conjugates Of Bpa and Bmpmentioning
confidence: 89%
See 1 more Smart Citation
“…However, whether the oxygen has been added to the internal or terminal carbon cannot be ascertained from the MS/MS spectrum. Ortiz de Montellano et al, (1982) have previously reported that if the oxygen atom is added to the internal carbon, the heme will be alkylated, and if the oxygen is added to the terminal carbon, the protein will be modified (Ortiz de Montellano and Komives, 1985;CaJacob et al, 1988;Chan et al, 1993). Because a protein adduct was identified in this case, the structure proposed for the GSH conjugate has the oxygen inserted into the terminal carbon as shown in Fig.…”
Section: Lc/ms/ms Analysis Of Gsh Conjugates Of Bpa and Bmpmentioning
confidence: 89%
“…Ortiz de Montellano et al (1982) have shown the formation of three metal-free regioisomers as a result of prosthetic heme alkylation after administration of ethchlorvynol to phenobarbital-treated rats. The first two isomers, which eluted very close together by HPLC, are identified as structures with the N-alkyl group on the vinyl-substituted pyrrole rings (A and B).…”
Section: Discussionmentioning
confidence: 99%
“…The iron-porphyrin complexes have been unambiguously identified as o-iron(III)-CH3 and o-iron(III)-CsHS complexes (Scheme 1) [15]. Moreover, evidence has been provided for similar o-phenyl [2,17] and o-methyl (our unpublished results) structures for the corresponding hemoglobin or myoglobin complexes. This analogy leads us to propose a cytochrome P450-Fe(III)-R structure with R=CH, or C,H,, for the complexes derived from reactions of microsomal cytochrome P450 with methylhydrazine or phenylhydrazine derivatives, which exhibit a Soret peak around 480nm.…”
Section: Nature Of' the Cytochrome P450 Complexes Exhibiting A Soret mentioning
confidence: 92%
“…Most importantly, these losses are associated with accumulation in the liver (or in incubations with tissue microsomes) of a green, red-fluorescing pigment (Tables 1 and 2). Isolation and characterization by UV-visible, mass spectrometric and NMR methods of several of these pigments has shown that in all of them the acetylene is covalently attached to one of the nitrogen atoms of protoporphyrin IX, the framework of the prosthetic heme group of the enzyme (e.g., Ortiz de Montellano et al 1979, 1982a, 1982bKunze 1980b, 1981b;Kunze et al 1983). In these adducts, the terminal carbon of the acetylene is attached to a porphyrin ring nitrogen atom and the internal carbon of the acetylene is present as a carbonyl group, as shown for the adduct obtained with propyne in Figure 15.…”
Section: Prosthetic Heme Alkylation By Acetylene and Monosubstituted mentioning
confidence: 99%
“…The four pyrrole rings of the porphyrin are labeled A-D. In this instance, the covalent bond was formed exclusively with pyrrole ring A, but other pyrrole rings can be alkylated in other adducts (e.g., Ortiz de Montellano et al 1982a). Schematic mechanism for autocatalytic alkylation of the heme prosthetic group of cytochrome P450 in the oxidation of a terminal acetylene.…”
Section: Specificitymentioning
confidence: 99%